2018
DOI: 10.1158/1535-7163.mct-17-0906
|View full text |Cite
|
Sign up to set email alerts
|

Nigericin Exerts Anticancer Effects on Human Colorectal Cancer Cells by Inhibiting Wnt/β-catenin Signaling Pathway

Abstract: Nigericin, an antibiotic derived from , which works by acting as an H, K, and Pb ionophore, has exhibited promising anticancer activity. The main purpose of this study is to investigate its inhibitory effects on Wnt/β-catenin signaling pathway in colorectal cancer cells and clarify the underlying mechanism. We exposed two colorectal cancer lines (SW620 and KM12) to increasing concentrations of nigericin for different time periods and the 50% inhibiting concentration (IC) values were evaluated. Our data showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Monensin was identified as a selective antineoplastic agent in prostate cancer cell line models 32 and more recently as a selective inhibitor of cancer stemness in induced cancer stem-like tumorspheres 27 . The anti-EMT or anti-CSC properties of nigericin have been studied in different models 3336 . Thus, this family of monovalent cation ionophores has repeatedly demonstrated cytotoxic effects against cancer cells exhibiting EMT-like or CSC phenotypes although the precise mechanism(s) remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Monensin was identified as a selective antineoplastic agent in prostate cancer cell line models 32 and more recently as a selective inhibitor of cancer stemness in induced cancer stem-like tumorspheres 27 . The anti-EMT or anti-CSC properties of nigericin have been studied in different models 3336 . Thus, this family of monovalent cation ionophores has repeatedly demonstrated cytotoxic effects against cancer cells exhibiting EMT-like or CSC phenotypes although the precise mechanism(s) remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A newly study by Yakisich et al demonstrated that nigericin might be used in a co-therapy model of lung cancer in combination with other chemotherapeutic agents [27]. Coincidentally, our lab also implied that Wnt/β-catenin signaling might have an essential role in colorectal cancer progression, and nigericin exerted anticancer effects on colorectal cancer cells by directly targeting the β-catenin destruction complex [28]. Furthermore, our recent study has proved the potential toxicity of nigericin on human PC, and revealed the molecular mechanism of nigericin toward PC cells from the perspective of circRNA (31533620).…”
Section: Discussionmentioning
confidence: 56%
“…A newly study by Yakisich et al demonstrated that nigericin might be used in a co-therapy model of lung cancer in combination with other chemotherapeutic agents ( 27 ). Coincidentally, our lab also implied that Wnt/β-catenin signaling might have an essential role in colorectal cancer progression, and nigericin exerted anti-cancer effects on colorectal cancer cells by directly targeting the β-catenin destruction complex ( 28 ). Furthermore, our recent study has proved the potential toxicity of nigericin on human PC, and revealed the molecular mechanism of nigericin toward PC cells from the perspective of circRNA ( 23 ).…”
Section: Discussionmentioning
confidence: 95%